2011
DOI: 10.1007/s00264-011-1452-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kirschner wires and AO cannulated screw internal fixation for displaced lateral humeral condyle fracture in children

Abstract: Purpose This retrospective study compares Kirschner wires versus 3.5-mm diameter AO cannulated screw internal fixation in treatment for the displaced lateral humeral condyle fractures. Methods The study included 62 patients (42 boys, 20 girls; mean age 6.93 years; age range two to 14 years) with displaced lateral humeral condyle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 27 publications
(31 reference statements)
1
70
0
3
Order By: Relevance
“…Many units also believe that any fracture with more than 2 mm of displacement should be managed with internal fixation [8]. This can be achieved using AO cannulated screws or Kirschner wires (K-wires) [9]. In our unit, K-wire fixation is the modality of choice.…”
Section: Introductionmentioning
confidence: 98%
“…Many units also believe that any fracture with more than 2 mm of displacement should be managed with internal fixation [8]. This can be achieved using AO cannulated screws or Kirschner wires (K-wires) [9]. In our unit, K-wire fixation is the modality of choice.…”
Section: Introductionmentioning
confidence: 98%
“…[11][12][13] Although closed reduction for displaced fractures remains controversial, recent studies have shown promising results. [12][13][14][15] Compression is important in these small, articular fractures, and the optimal mode of fixation for maintaining fracture reduction is debated. 14-17 Several constructs (eg, multiple smooth pins, single lag screw, and threaded pins) have been described.…”
mentioning
confidence: 99%
“…Li et al [34] compared wire fixation and screw fixation, and found no difference in the results. However, the metaphyseal fragment was often too small to be purchased by a screw.…”
Section: Discussionmentioning
confidence: 98%